- #1

insertnamehere

- 50

- 0

I used the equation

V(final) = V(initial) - gt

where V(initial)=0

therefore V(final)= -9.8t

and V^2(final) = V^2(initial) - 2gh

h= -4m

V(final)= -9.8t

so i replaced these values in the equation, and i find t= 0.9035 seconds

To find T, I simply multiplied 0.9035 sec by 2. However, my answer does not correspond that what it says in the book, and now I'm lost! Can someone help me by telling me if my method is right or wrong? I would really appreciate it!

Thank you!